The psychosocial well-being of older adults in COVID-19 and the 'new normal' - TAN, Micah (Institutional Knowledge at Singapore Management University, 2021)
Early research into COVID-19 has focused predominantly on the immediate and direct physical health effects of the pandemic, as compared to the wider, indirect effects of the pandemic on general well-being brought about by the various measures put in place to contain the virus. In terms of policies, focus has also been placed largely on containment and broad based policies for the entire population. As experts increasingly recognize that the pandemic will be a protracted event (The Straits Times, 2021), however, there is a need for stakeholders to place greater emphasis on the indirect effects of COVID-19 that will likely continue to shape well-being in the ‘new normal’. As the impact of these effects has been argued to vary both quantitatively and qualitatively on different groups (Douglas et al., 2020), it is thus important for researchers to make better sense of how particular groups of individuals have been affected, beginning with those deemed most at risk. For these reasons, the present research endeavors to understand how older adult well-being has been impacted during COVID-19, especially during the post-lockdown transitionary period into the ‘new normal’. Only by better understanding how such wider effects are impacting older adults can appropriate policy approaches be formulated to adequately ensure for the well-being of older adults. This paper hence offers an understanding of some factors that have exacerbated the decline in psychosocial well-being experienced by older adults in Singapore during the COVID-19 pandemic and offers recommendations for policy interventions aimed at assisting older adults transition into the ‘new normal’. To provide context, the analysis will begin with an overview of the trends in psychosocial well-being among older adults in Singapore over 2020. Subsequently, the paper will explore in greater detail two significant issues in relation to the psychosocial well-being of older adults during the pandemic: social isolation, and psychological resilience after the circuit-breaker. Finally, the paper concludes by offering brief policy recommendations based on these findings. Findings are derived from the Singapore Life Panel®, a population representative monthly survey that tracks the lives of Singaporeans aged 55 to 75 to better understand the factors that shape the well-being of older adults, with a monthly average of 7,500 responses.